TNFR2 blockade of regulatory T cells unleashes an antitumor immune response after hematopoietic stem-cell transplantation - Moatti, A; Debesset, A; Pilon, C; Beldi-Ferchiou, A; Leclerc, M; Redjoul, R; Charlotte, F; To, NH; Bak, A; Belkacemi, Y; Salomon, BL; Issa, F; et al. (BMJ Publishing Group, 2022)
Background targeting immune checkpoints that inhibit antitumor immune responses has emerged as a powerful new approach to treat cancer. We recently showed that blocking the tumor necrosis factor receptor-type 2 (tnfr2) pathway induces the complete loss of the protective function of regulatory t cells (tregs) in a model of graft-versus-host disease (gvhd) prevention that relies on treg-based cell therapy. Here, we tested the possibility of amplifying the antitumor response by targeting tnfr2 in a model of tumor relapse following hematopoietic stem-cell transplantation, a clinical situation for which the need for efficient therapeutic options is still unmet. Method we developed appropriate experimental conditions that mimic patients that relapsed from their initial hematological malignancy after hematopoietic stem-cell transplantation. This consisted of defining in allogeneic bone marrow transplantation models developed in mice, the maximum number of required tumor cells and t cells to infuse into recipient mice to develop a model of tumor relapse without inducing gvhd. We next evaluated whether anti-tnfr2 treatment could trigger alloreactivity and consequently antitumor immune response. In parallel, we also studied the differential expression of tnfr2 on t cells including treg from patients in post-transplant leukemia relapse and in patients developing gvhd. Results using experimental conditions in which neither donor t cells nor tnfr2-blocking antibody per se have any effect on tumor relapse, we observed that the coadministration of a suboptimal number of t cells and an anti-tnfr2 treatment can trigger alloreactivity and subsequently induce a significant antitumor effect. This was associated with a reduced percentage of activated cd4+ and cd8+ tregs. Importantly, human tregs over-expressed tnfr2 relative to conventional t cells in healthy donors and in patients experiencing leukemia relapse or cortico-resistant gvhd after hematopoietic stem cell transplantation. Conclusions these results highlight tnfr2 as a new target molecule for the development of immunotherapies to treat blood malignancy relapse, used either directly in grafted patients or to enhance donor lymphocyte infusion strategies. More widely, they open the door for new perspectives to amplify antitumor responses against solid cancers by directly targeting tregs through their tnfr2 expression.